KAJIAN SISTEM KINERJA PLTS OFF-GRID 1 kWp DI STT-PLN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2018)
The Solar Power Plant Off-Grid 1 kWp at STT-PLN is one of the power plants built at STT-PLN to support renewable energy research, especially solar power generation. Since the solar power plant Off-Grid 1 kWp in STT-PLN has not yet known the optimum potential of electrical energy, the final yield (YF), the performance ratio (PR), and the efficiency of the system which is the parameters of a plant's performance Solar power. It is therefore necessary to analyze the performance of the solar power plant Off-Grid 1 kWp in STT-PLN, in order to know the operating system and the constraints that occur in the solar power plant Off-Grid 1 kWp in STT-PLN. To know the working parameters of Off-Grid 1 kWp in STT-PLN then do the research before and after maintenance of solar powerplant. Where final yield (YF), performance ratio (PR) before maintenance is 1.71343 Wh / Wp.day; 51.78%. While after maintenance of 3.10121 Wh / Wp.day; And 79.29%. From this research also obtained the efficiency of Off-Grid 1 kWp solar power system in STTPLN as a whole by 80,40%.